Luxury Consumption: Staging Experiences & Creating Value for Millennials using a Customer-Dominant Logic. - Rodriguez Valdez, Adriana (2015)
The purpose of this study is to examine the role of luxury brands in the Millennial luxury consumers’ lifeworld and to understand the importance of the customer experience for the Millennial luxury consumers within the value creation process. Moreover, this research aims to fill the gap in the present literature between the existing luxury brand management and value creation process literature incorporating the Millennial consumers lifeworld.